ON THE WORK OF MALIKAXON ZIYOYEVA, A TRUE FEMALE MUSICIAN OF THE CENTURY - Makhmudova Farangiz Nuriddin qizi (Western European Studies, 2025)
This article examines the traditional oral paths of professional music, their role within the master-apprentice system, and their integration into contemporary music education. The study results show that traditional methods effectively develop students’ creative and technical skills. At the same time, the use of modern technologies and folkloric materials enhances the quality of music education.
Keywords: oral tradition; professional music; master-apprentice